THE INFLUENCE OF CORPORATE GOVERNANCE AND AUDIT QUALITY ON THE INTEGRITY OF FINANCIAL STATEMENTS - Dwi Urip Wardoyo; I Putu Diva Arimbawa Putra; Camelia Aini (Globalwriting Academica Consulting & Publishing, 2021)
Integrity of financial statements is a financial report that describes financial data correctly and honestly and does not side with any party. This study aims to determine the effect of corporate governance with indicators of institutional ownership and audit quality on the integrity of financial statements in the sub-sector of companies listed on the Indonesia Stock Exchange in 2018-2019. The method used for sample selection was purposive sampling and 18 samples were observed for two years so that 36 were observed. In analyzing research data, the analytical technique used is panel data regression analysis using Eviews 12 software. The results show that simultaneously corporate governance with indicators of institutional ownership and audit quality has no effect on the integrity of financial statements. Partially, corporate governance with indicators of institutional ownership has no effect on the integrity of financial statements and audit quality with indicators of auditor specialization has no effect on the integrity of financial statements. The results of this study are expected to play a role for companies to know financial data correctly.